fMRI study of pain threshold in the presence and absence of the loved one - Tamam, Sofina (2016)
Laser-induced heat pain and functional magnetic resonance imaging (fMRI) techniques were used to investigate the modulation of pain response under two different conditions. One condition was when the participants were not accompanied by their loved ones (Alone condition) and the other condition was when the participants were accompanied by their loved ones (Support condition) during pain stimulus delivery inside the MRI gantry. Th:YAG laser was used as pain stimuli with its light beam targeted onto the dorsum of the right hand. An experimental paradigm utilizing block design was first developed for the fMRI scan. 17 female subjects participated (mean age 20.59; SD 2.85 years) and the pain threshold was determined prior to scanning. The Experience Closed Relationship - Relationship Structure (ECR - RS) test and USM personality inventory questionnaires (USMaP-i) were given prior to fMRI scanning. Statistical Parametric Mapping (SPM) version 8 with Dynamic Causal Modelling (DCM) approach was used to investigate the connectivity between activated regions and one optimum connectivity model was identified finally. It was found that individual responses to pain may be divided into two categories. The group accompanied by a family member as the loved one have lower pain threshold in Support condition, representing Love Hurts; while the group accompanied by a partner have higher pain threshold in the same condition, representing Love Heals. Extraversion personality was found to reduce the response to pain stimulation when accompanied by the loved one. All participants showed activations in areas associated with pain processing. In Alone condition, ACC, MCC,INS, AMY, VLPFC and HIP were activated, while in Support condition, INS, VLPFC, SII, THA and supramarginal gyrus were activated. DCM analysis revealed that Love Hurts involved activations in THA, PHG and HIP while Love Heals involved activations in all parts of cingulate cortex. BMS showed that Love Heals could be represented by a cortical network involving the intrinsic connectivity of ACC → PCC → MCC and ACC → MCC. In conclusion, the present study revealed that having a loved one nearby modulates pain differently depending on the personality of the individual and the type of relationship with the loved one. More interestingly, this study discovers a new possible cortical network for Love Heals